Use of indigenous knowledge in strategies for disaster risk reduction for flood disaster: the study of Tharu community of Bardiya district of Nepal - Dhungel, Rachhita (BRAC University, 2012)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2011.